2021
DOI: 10.1093/braincomms/fcab117
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer type 1 and neurodegeneration: consequences of deficient DNA repair

Abstract: Numerous cellular processes including toxic protein aggregation and oxidative stress have been studied extensively as potential mechanisms underlying neurodegeneration. However, limited therapeutic efficacy targeting these processes has prompted other mechanisms to be explored. Previous research has emphasized a link between cellular senescence and neurodegeneration, where senescence induced by excess DNA damage and deficient DNA repair results in structural and functional changes that ultimately contribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 161 publications
(184 reference statements)
2
12
0
Order By: Relevance
“…Additionally, as this study identified reduced DNA repair pathways in the injured brain, this study suggests that inefficient DNA repair may further confer susceptibility to brain dysfunction after TBI. This poses important questions for understanding risk factors, as many DNA repair factors are naturally polymorphic or may be affected by factors such as sex (Fischer and Riddle, 2018 ; Leung and Hazrati, 2021 ), age (Fischer and Riddle, 2018 ), and lifestyle factors such as substance use (Madden et al, 1979 ).…”
Section: Cellular Senescence As a Pathophysiological Mechanism In Mtbimentioning
confidence: 99%
“…Additionally, as this study identified reduced DNA repair pathways in the injured brain, this study suggests that inefficient DNA repair may further confer susceptibility to brain dysfunction after TBI. This poses important questions for understanding risk factors, as many DNA repair factors are naturally polymorphic or may be affected by factors such as sex (Fischer and Riddle, 2018 ; Leung and Hazrati, 2021 ), age (Fischer and Riddle, 2018 ), and lifestyle factors such as substance use (Madden et al, 1979 ).…”
Section: Cellular Senescence As a Pathophysiological Mechanism In Mtbimentioning
confidence: 99%
“…Oxidative stress and genotoxic damage are key initiators of senescence. Consistent with this possibility, the polymorphic nature of DNA repair factors and sex-differences in genomic instability may be responsible for the clinical heterogeneity in outcomes after TBI ( Fischer and Riddle, 2018 ; Leung and Hazrati, 2021 ). Thus, proactive targeting of the early genotoxic stress response may restrain the initiation of cellular senescence/SASP as a “first domino” that potentiates progressive neurodegeneration at all levels of TBI.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 90%
“…This suggests that the BRCA mutation, itself, is detrimental to brain integrity. A number of in vitro studies have shown that BRCA1 both 1) accumulates in AD pathologies and tauopathies in general 17,22,24 and 2) is generally reduced in patients with AD 17,20,21,24 . Additionally, reductions of BRCA1 within the brain may be related to learning and memory deficits in mixed-sexed rodents 21,24 .…”
Section: Discussionmentioning
confidence: 99%
“…While there is less evidence for BRCA2 and dementia, it has been proposed that loss of the BRCA2-mediated DNA repair mechanism may lead to neurodegeneration 19 . Thus, in addition to increased risk due to the sudden loss of E2, there is evidence from both in vitro and in vivo rodent and human studies suggesting that carrying BRCAm may further increase the risk of developing late life dementia 17,[20][21][22]24 . Our results in this regard are very preliminary but support the previous literature on BRCAm and brain changes and raise the interesting possibility that women with the BRCA mutation and BSO may grapple with a double indemnity: issues with gene repair and E2 loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation